Mutation of c.244G>T in NR5A1 gene causing 46, XY DSD by affecting RNA splicing - Yu, Bingqing; Gao, Yinjie; Mao, Jiangfeng; Wang, Xi; Nie, Min; Wu, Xueyan (Orphanet journal of rare diseases, 2021)
To identify the pathogenic mechanism of the c.244G>T mutation in NR5A1 gene found in a Chinese patient with 46, XY disorders of sex development (DSD). Genomic DNA was extracted from a Chinese 46, XY DSD patient. Targeted next-generation and Sanger sequencing were performed to investigate and validate the gene mutation causing 46, XY DSD, respectively. In silico tools were used to predict the pathogenicity of the variant. Dual luciferase reporter gene assay and minigene splicing reporter assay were used to identify the pathogenicity of the variant. A novel heterozygous variant, c.244G>T (p.Ala82Ser), in NR5A1 gene was detected in the 46, XY DSD patient. Four of five silico tools predicting pathogenicity of missense variants indicated that the variant was pathogenic. However, in vitro functional study showed that p.Ala82Ser did not affect the transcriptional activity of NR5A1. In silico tools predicting the potential splicing loci revealed that c.244G>T led to aberrant splicing of NR5A1 RNA. Minigene splicing reporter assay confirmed that c.244G>T resulted in the deletion of exon2 or deletion of 19 nucleotides in 3' end of exon2. Mutation of c.244G>T in NR5A1 results in 46, XY DSD by inducing abnormal splicing of NR5A1 RNA instead of amino acid substitution of NR5A1.